Behavioral Intention and Adoption of Clinical Informatics Tools: A Study in Regional Public Municipality Clinics (Scientific Journal of Informatics, 2024)
Purpose: The healthcare sector is vital for addressing public health emergencies and improving overall health outcomes. This paper aims to explore the factors that influence the adoption of clinical informatics by healthcare professionals in public clinics within a KwaZulu Natal municipality in South Africa. The paper adopted the Unified Theory of Acceptance and Use of Technology (UTAUT) to understand determinants of behavioral intention to use, and actual usage of these clinical informatics tools by the sampled healthcare professionals.Methods: The paper adopted a mixed-methods approach to answer the research questions, both primary quantitative and secondary qualitative data was collected and analysed. Surveys and interviews were conducted with 67 sampled healthcare professionals including doctors, nurses, administrative staff and 10 managers to obtain the primary quantitative data and secondary qualitative data respectively. SPSS was used to analyse the quantitative data and thematic content analysis was used to analyse for the qualitative data.Result: Results indicate that the constructs of UTAUT positively influence healthcare workers’ intention to use and use of clinical informatics tools, these include in the order of their influence, performance expectancy, effort expectancy, social influence and facilitating conditions. While clinical informatics tools are available and frequently used by healthcare workers, significant challenges are mentioned to impede their effective adoption. These challenges include insufficient hardware, lack of awareness and training about ICT applications, and limited access to data network infrastructure such as Wi-Fi hotspots and routers.Novelty: The novelty of this research lies in its comprehensive analysis of both the behavioral and infrastructural factors affecting the adoption of clinical informatics in a specific municipal context. Conducted in a municipality that serves both rural and urban communities, this study provides practical recommendations to overcome identified adoption barriers. The findings contribute to developing strategies for the adoption and provision of clinical informatics tools to improve healthcare delivery in South Africa.